2013
DOI: 10.1007/s10142-013-0333-4
|View full text |Cite
|
Sign up to set email alerts
|

Genes encoding the production of extracellular polysaccharide bioflocculant are clustered on a 30-kb DNA segment in Bacillus licheniformis

Abstract: Bioflocculants are special high-molecular weight polymers produced by microorganisms. Despite the fact that several types of bioflocculants from different species of bacteria have been reported, there is a large gap in our knowledge regarding the molecular machine responsible for the production of bioflocculants. To investigate genes involved in bioflocculant synthesis, a fosmid library was generated from Bacillus licheniformis genomic DNA and screened for the production of bioflocculant. Four positive clones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…15 Similarly, the flocculation properties of g-PGA (6.2 3 10 6 Da) derived from B. subtilis R 23 indicated that g-PGA can be used in wastewater treatment plants and downstream processing of food and fermentation industries. 12 In this study, B. licheniformis CGMCC 2876, a strain that was previously identified to synthesize a polysaccharide bioflocculant in our laboratory, 16,17 was found to produce g-PGA with even higher FA. The effects of nutrients and chemical compositions on the production and flocculation activity of the g-PGA from B. licheniformis CGMCC 2876 were focused, and the flocculating efficiency of g-PGA was compared with commonly used chemically synthesized flocculant (PAM) in the sugar refinery process.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…15 Similarly, the flocculation properties of g-PGA (6.2 3 10 6 Da) derived from B. subtilis R 23 indicated that g-PGA can be used in wastewater treatment plants and downstream processing of food and fermentation industries. 12 In this study, B. licheniformis CGMCC 2876, a strain that was previously identified to synthesize a polysaccharide bioflocculant in our laboratory, 16,17 was found to produce g-PGA with even higher FA. The effects of nutrients and chemical compositions on the production and flocculation activity of the g-PGA from B. licheniformis CGMCC 2876 were focused, and the flocculating efficiency of g-PGA was compared with commonly used chemically synthesized flocculant (PAM) in the sugar refinery process.…”
Section: Introductionmentioning
confidence: 73%
“…In this study, B. licheniformis CGMCC 2876, a strain that was previously identified to synthesize a polysaccharide bioflocculant in our laboratory, was found to produce γ‐PGA with even higher FA. The effects of nutrients and chemical compositions on the production and flocculation activity of the γ‐PGA from B. licheniformis CGMCC 2876 were focused, and the flocculating efficiency of γ‐PGA was compared with commonly used chemically synthesized flocculant (PAM) in the sugar refinery process.…”
Section: Introductionmentioning
confidence: 74%
“…; Yan et al. ). The gene products, mostly enzymes, are involved in the formation of polysaccharides by sequential addition of sugars to membrane anchored repeating units which are then exported (Cerning ).…”
Section: Molecular Biology and Synthesis Of Bioflocculantmentioning
confidence: 99%
“…In the latter phase of polysaccharide fermentation, the flocculating activity decreases because of the degradation of this bioflocculant. At the same time, a gene encoding β-glucosidase (Bgl.bli1) in a bioflocculant-producing clone was predicted to be involved in polysaccharide bioflocculant dissimilation (Yan et al 2013). The present study describes the cloning, heterologous expression and biochemical characterization of this β-glucosidase.…”
Section: Introductionmentioning
confidence: 99%